2022
DOI: 10.1021/acsnano.2c01332
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Engineered Nanocrystal Three-Dimensional Superlattices via Ligand Conformation and Reactivity

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 96 publications
2
26
0
Order By: Relevance
“…Our group has recently demonstrated that the micro-mechanical properties of periodically arranged NCs can be significantly boosted by creating a sub-nm thin, crosslinked, organic network in-between them, using small C-18 fatty acids or phospholipids as surface functionality. [26][27][28][29] The crosslinking of self-assembled organo-functionalized NCs can be achieved by thermal annealing at moderate temperatures (150 -350 °C) and allows reaching record-high values of strength, hardness, and stiffness, while still maintaining the nano-characteristic functionalities and a moderate degree of fracture toughness. 5,[25][26][27][28][29][30][31][32][33] However, the interactions that dictate the nanobuilding blocks' ordering during the first step of the nanocomposite's development (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has recently demonstrated that the micro-mechanical properties of periodically arranged NCs can be significantly boosted by creating a sub-nm thin, crosslinked, organic network in-between them, using small C-18 fatty acids or phospholipids as surface functionality. [26][27][28][29] The crosslinking of self-assembled organo-functionalized NCs can be achieved by thermal annealing at moderate temperatures (150 -350 °C) and allows reaching record-high values of strength, hardness, and stiffness, while still maintaining the nano-characteristic functionalities and a moderate degree of fracture toughness. 5,[25][26][27][28][29][30][31][32][33] However, the interactions that dictate the nanobuilding blocks' ordering during the first step of the nanocomposite's development (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] The crosslinking of self-assembled organo-functionalized NCs can be achieved by thermal annealing at moderate temperatures (150 -350 °C) and allows reaching record-high values of strength, hardness, and stiffness, while still maintaining the nano-characteristic functionalities and a moderate degree of fracture toughness. 5,[25][26][27][28][29][30][31][32][33] However, the interactions that dictate the nanobuilding blocks' ordering during the first step of the nanocomposite's development (i.e. self-assembly) do not provide structural control at larger length scales.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations